Persepsi Pegawai Pemerintah Kota Semarang Terhadap Penerapan Aplikasi Sistem Informasi Manajemen Kepegawaian Berbasis Teknologi (Simpatik) - Aldila Latifa Triana; Yuwanto - - (Journal of Politic and Government Studies, 2020)
Application information system based personnel management technology which is then called Simpatik is a program that aims to provide convenience to employees of the Government of Semarang to manage the needs of personnel services. This application is an update of previous personnel service applications that are then synchronized with each other by implementing Single Sign On (SSO) technology so that there is also some new employee service innovations contained within the Simpatik application. The main focus of this research is the context the perception of employees of the Regional Secretariat of Semarang City related to the implementation of Simpatik application as a base of employment services as well as supporting factors and factors inhibiting the formation of employee perception in using Simpatik application. This research approach uses quantitative descriptive with sampling techniques using purposive sampling then obtained by 149 respondents from 237 populations while for data collection techniques using questionnaires, interviews, and documents. From this research, it is explained that the employees of the Regional Secretariat of Semarang City have had a good perception of the application of Simpatik application for employment services. This is supported by the results of research that most employees have a perception in a high category with a percentage of 54,4%. When reviewed from the indicator of employee knowledge fell into a very high category of 73,8%. When reviewed from employee experience while using the Simpatik application, most have a high perception with a percentage of 44,3%. Then, employee perception if reviewed from motivation, entered into the category with a percentage of 33,6%. Then based on the evaluation indicator entered into a very high category of 48,3%. The perception of employees of the Regional Secretariat of Semarang City is formed because of the internal factors of individual employees, namely based on the knowledge, experience, motivation and evaluation that employees have. While external factors are formed due to the influence of the individual external environment.